3D kinematic analysis of salto backward in acrobatic rock and roll: a case study - Adéla Chlapcová; Peter Olej; Oľga Kyselovičová (Physical Education of Students, 2023)
Background and Study Aim. The aim of the study was to determine and compare basic kinematic characteristics in the key phases of the acrobatic element Salto backward tucked.